1992
DOI: 10.1136/adc.67.7.952
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of suppurative lymphadenitis after a change of BCG vaccine.

Abstract: BCG vaccines are the oldest vaccines in use today, but the protective effect of the vaccination is still controversial. The risk of contracting tuberculosis is low compared with the possible complications after this vaccination. In Austria the formerly used BCG vaccine was not available in the required amount and another vaccine was released by the drug authorities. This product, with a more virulent strain, was used between August and December 1990, and this increased the incidence of complications. Eighty f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 13 publications
1
21
1
Order By: Relevance
“…Analysis of all epidemics has revealed that BCG lymphadenitis is an exaggerated response to a more immunogenic strain that was introduced in the immunization schedule [18][19][20]; this could explain this outbreak of BCG lymphadenitis with the introduction of a new BCG vaccine strain. Study was carried out to evaluate the course of BCG lymphadenitis occurring during this outbreak and its response to different management strategies as there are no clear evidence-based data for the best treatment of these infants.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of all epidemics has revealed that BCG lymphadenitis is an exaggerated response to a more immunogenic strain that was introduced in the immunization schedule [18][19][20]; this could explain this outbreak of BCG lymphadenitis with the introduction of a new BCG vaccine strain. Study was carried out to evaluate the course of BCG lymphadenitis occurring during this outbreak and its response to different management strategies as there are no clear evidence-based data for the best treatment of these infants.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the present study was to determine whether the strains divergences may influence their relative immunogenicity [12, 13], virulence [14, 15], and viability [16], factors that must be considered for the design and improvement of a vaccine against TB.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This complication is known to be related to the type of vaccine, dose and route of administration. [4][5][6][7] Host factors include the age at which it is given and the immunological status of the recipient. Normal newborns even those who are immunologically normal are known to have higher incidence of complications as compared to older infants and children.…”
mentioning
confidence: 99%